Best Practice in the chemical characterisation of extracts used in pharmacological and toxicological research—The ConPhyMP—Guidelines12 - Heinrich, Michael; Jalil, Banaz; Abdel-Tawab, Mona; Echeverria, Javier; Kulić, Žarko; McGaw, Lyndy J.; Pezzuto, John M.; Potterat, Olivier; Wang, Jia-Bo (Frontiers in Pharmacology, 2022)
Background: Research on medicinal plants and extracts derived from them differs from studies performed with single compounds. Extracts obtained from plants, algae, fungi, or lichens pose some unique challenges: they are multicomponent mixtures of active, partially active and inactive substances, and the activity is often not exerted on a single target. Their composition varies depending on the method of preparation and the plant materials used. This complexity and variability impact the reproducibility and interpretation of pharmacological, toxicological and clinical research. Objectives: This project develops best practice guidelines to ensure reproducibility and accurate interpretations of studies using medicinal plant extracts. The focus is on herbal extracts used in pharmacological, toxicological, and clinical research. Specifically, the consensus-based statement focuses on defining requirements for: (1) Describing the plant material/herbal substances, herbal extracts and herbal medicinal products used in these studies, and (2) Conducting and reporting the phytochemical analysis of the plant extracts used in these studies. The process and methods: We developed the guidelines through the following process: (1) The initial distinction between the three types of extracts, initially conceptualised by the lead author (MH), led the development of the project as such. (2) A survey among medicinal plant researchers to gather global perspectives, opportunities, and overarching challenges faced in characterising medicinal plant extracts under different laboratory infrastructures. The survey responses were central to developing the guidelines and were reviewed by the core group; (3) A core group of 9 experts met monthly to develop the guidelines through a Delphi process; and (4) The final draft guidelines, endorsed by the core group, were also distributed for feedback and approval to an extended advisory group of 20 experts, including many journal editors. Outcome: The primary outcome is the ‘Consensus statement on the Phytochemical Characterisation of Medicinal Plant extracts’ (ConPhyMP) which defines the best practice for reporting the starting plant materials and the chemical methods recommended for defining the chemical compositions of the plant extracts used in such studies. The checklist is intended to be an orientation for authors in medicinal plant research as well as peer reviewers and editors assessing such research for publication.